Unicyclic Graphs with the Fourth Extremal Wiener Indices - Guangfu Wang; Yujun Yang; Yuliang Cao; Shoujun Xu (Journal of Chemistry)
A graph is called unicyclic if the graph contains exactly one cycle. Unicyclic graphs with the fourth extremal Wiener indices are characterized. It is shown that, among all unicyclic graphs with n≥8 vertices, C5Sn−4 and C2u1,u2S3,Sn−4 attain the fourth minimum Wiener index, whereas C3u1,u2P3,Pn−4 attains the fourth maximum Wiener index.